Fanconi Syndrome Leading to Hypophosphatemic Osteomalacia Related to Tenofovir Use - Mana Rao; Liam Dadey; Thomas Glowa; Peter Veldkamp (MDPI AG, 2021)
Tenofovir disoproxil fumarate (TDF) is used worldwide to treat and prevent Human Immunodeficiency Virus (HIV) infection. Fanconi syndrome is a complication of TDF use and is characterized by inadequate reabsorption of glucose, phosphate and protein in the proximal tubule of the kidney which may eventually lead to osteomalacia manifested by symptoms of pain, muscular weakness and difficulty ambulating. We present a patient with severe osteomalacia due to progressive and unrecognized Fanconi's syndrome, who responded rapidly to TDF withdrawal, oral phosphate repletion and calcitriol. With the widespread use of TDF-containing antiviral regimens, it is critically important that physicians adhere to screening recommendations to detect early Fanconi syndrome, and recognize symptoms of osteomalacia as a serious complication.